Migrants seeking help for cognitive disturbances: exploratory data from an Italian memory clinic - Canevelli, Marco; Zaccaria, Valerio; Ruocco, Ciro; Valletta, Martina; Gasparini, Marina; Vanacore, Nicola; Cesari, Matteo; Bruno, Giuseppe (Neurological sciences, 2019)
Introduction The phenomenon of dementia occurring in migrants and minority groups constitutes an emerging issue for Western countries. Nevertheless, it has been poorly explored from the perspective of “real-world” clinical services. We aimed to quantify the number of migrants from LMIC attending an Italian university memory clinic and to document its modifications over time. Methods All the subjects undergoing a first neurological and cognitive assessment between 2001 and 2017 were considered for the present analyses. Results The proportion of subjects from LMIC performing a first cognitive evaluation was found to remain substantially stable between 2001 and 2017. No statistically significant difference was found between “HIC” and “LMIC” individuals with regard to sociodemographic and clinical characteristics. Conclusion These findings seem to indicate that cognitive disorders in LMIC migrants still constitute a marginal public health issues for Italian dementia services. Nevertheless, the identification of eventual sociocultural and healthcare barriers may help to understand the real magnitude and relevance of this phenomenon.